Pengaruh Manual Osilasi Vertebre Terhadap Penurunan Nyeri Terhadap Nyeri Punggung Bawah di RSUD KRMT Wongsonegoro - Widya Ervianta; Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Background: Lower back pain (NPB) Ischialgia is a pinched ischialgia nerve in the lower back area which causes the buttocks, thighs, lower legs and even feet to become tingling, painful, and sometimes causing weakness. Manipulation is a term to cover all forms of passive movement techniques used to treat musculoskeletal disorders. Manipulation techniques are passive movement techniques that are carried out quickly so that the movement is completed before the patient can prevent it. The movement that occurs should not exceed the physiological range of motion of the joint. G.D. Maitland (1997), The aim is to determine the effect of physiotherapy management on manual therapy in cases of lower back pain. Two group pre test and post test method. RESEARCH PLACE: Physiotherapy polyclinic, KRMT Wongsonegoro Hospital. TIME: Measuring instrument: Visual Analouge Scale (VAS). Results: treatment using the Mann-Whtney test. With confidence interval (CI) (95%) The results of the study revealed that there was a significant difference in pain in group 1 (p = 0.00) and group 2 (p = 0.00). But there was no significant difference between the two groups in pain improvement (p = 0.00), so there was a better effect between the two groups. Conclusion: It is concluded that manual therapy is useful in treating patients with lower back pain to reduce pain in two groups. The targeted outcome is publication in national indexed journals Sinta and HAKI. The TKT target for implementing this gamelan accompaniment exercise is level 2